Osteopontin Promotes Left Ventricular Diastolic Dysfunction Through a Mitochondrial Pathway - Yousefi, Keyvan; Irion, Camila I.; Takeuchi, Lauro M.; Ding, Wen; Lambert, Guerline; Eisenberg, Trevor; Sukkar, Sarah; Granzier, Henk L.; Methawasin, Mei; Lee, Dong I.; Hahn, Virginia S.; Kass, David A.; et al. (Journal of the American College of Cardiology, 2019)
Patients with chronic kidney disease (CKD) and coincident heart failure with preserved ejection fraction (HFpEF) may constitute a distinct HFpEF phenotype. Osteopontin (OPN) is a biomarker of HFpEF and predictive of disease outcome. We recently reported that OPN blockade reversed hypertension, mitochondrial dysfunction, and kidney failure in Col4a3−/− mice, a model of human Alport syndrome. The purpose of this study was to identify potential OPN targets in biopsies of HF patients, healthy control subjects, and human induced pluripotent stem cell–derived cardiomyocytes (hiPS-CMs), and to characterize the cardiac phenotype of Col4a3−/− mice, relate this to HFpEF, and investigate possible causative roles for OPN in driving the cardiomyopathy. OGDHL mRNA and protein were quantified in myocardial samples from patients with HFpEF, heart failure with reduced ejection fraction, and donor control subjects. OGDHL expression was quantified in hiPS-CMs treated with or without anti-OPN antibody. Cardiac parameters were evaluated in Col4a3−/− mice with and without global OPN knockout or AAV9-mediated delivery of 2-oxoglutarate dehydrogenase-like (Ogdhl) to the heart. OGDHL mRNA and protein displayed abnormal abundances in cardiac biopsies of HFpEF (n = 17) compared with donor control subjects (n = 12; p < 0.01) or heart failure with reduced ejection fraction patients (n = 12; p < 0.05). Blockade of OPN in hiPS-CMs conferred increased OGDHL expression. Col4a3−/− mice demonstrated cardiomyopathy with similarities to HFpEF, including diastolic dysfunction, cardiac hypertrophy and fibrosis, pulmonary edema, and impaired mitochondrial function. The cardiomyopathy was ameliorated by Opn−/− coincident with improved renal function and increased expression of Ogdhl. Heart-specific overexpression of Ogdhl in Col4a3−/− mice also improved cardiac function and cardiomyocyte energy state. Col4a3−/− mice present a model of HFpEF secondary to CKD wherein OPN and OGDHL are intermediates, and possibly therapeutic targets. [Display omitted]